Save and Spend: an e-book for college students / Noratasha Idris ... [et al.] - Idris, Noratasha; Zainudin, Balqis; Mohamad Zaffir, Nur Zahirah; Amir, Nur Izzati; Koe, Wei Loon (Universiti Teknologi MARA, Kedah, 2023)
Personal savings and money management are important as they enable us to achieve our financial objectives, get out of debt, and increase our savings. This innovation is an e-book. The name of this e-book is Save and Spend. It contains information on how to manage personal savings and how to use the “Money Manager” app for personal money management. Nowadays, most college students are facing financial problems and do not know how to manage their money. When college students are under constant financial pressure, it may have a negative impact on their personal life, such as causing them to have trouble sleeping because they worry about their financial situation and are unable to relax enough to fall asleep. Their financial problems may be caused by overspending due to a failure to allocate their savings. This e-book was developed with the intention of improving the learning process. The process of this e-book's education will be more interesting and participatory. The main objective of this e-book is to explain an idea or concept to reach the goal of personal financial learning. It also provides information on how to use “Money Manager” app. The uniqueness of this e-book compared to others is that it is accessible to everyone for free and can be searched online. This e-book benefits the community in terms of introducing and educating the students about financing, investing, money control, and avoiding debt while teaching them using “Money Manager” app for money management. This e-book can help them achieve financial stability and independence in the future. The target market is college students. We utilized the “Money Manager” app for money management to make it more fun and easier to use.